Barriers to comparing the usability of electronic health records. (29th August 2016) - Ratwani, Raj M; Hettinger, A Zachary; Fairbanks, Rollin J
Abstract : Despite the widespread adoption of electronic health records (EHRs), usability of many EHRs continues to be suboptimal, with some vendors failing to meet usability standards, resulting in clinician frustration and patient safety hazards. In an effort to increase EHR vendor competition on usability, recommendations have been made and legislation drafted to develop comparison tools that would allow purchasers to better understand the usability of EHR products prior to purchase. Usability comparison can be based on EHR vendor design and development processes, vendor usability testing as part of the Office of the National Coordinator for Health Information Technology certification program, and usability of implemented products. Barriers exist within the current certified health technology program that prevent effective comparison of usability during each of these stages. We describe the importance of providing purchasers with improved information about EHR usability, barriers to making usability comparisons, and solutions to overcome these barriers.